Analysis of the Application of Technology to the Learning Process of Elementary School Students in Facing the Computer-Based National Assessment Examination (CBNA) - Dika Dayanti; Miru, Sulaiman; Hadih, Suriyadi; Syamsuddin (PT. Global World Scientific, 2024)
This research was conducted to find out and analyze the application of technology to the learning process of elementary school students facing the CBNA (Computer-Based National Assessment) government program, which aims to map the quality of primary and secondary school education in Indonesia. This research aims to determine students' readiness to face CBNA and what factors are obstacles in preparing to face CBNA. This type of research is qualitative, with a case study approach regarding students' readiness to face CBNA. Preparations made by students facing CBNA include following socialization by teachers who serve as proctors and technicians. Then students take part in computer use training accompanied by a teacher, carried out after school. During this training, the teacher also provides motivational support to students so that they remain enthusiastic and not worry about facing CBNA. There are several obstacles to students' readiness in facing CBNA, namely, students have low technological literacy, limited computer equipment available, limited electricity sources as a resource for using computer devices, and limited internet networks, causing students not to be able to take part in the simulation on the CBNA page. Even though it is accompanied by If there are obstacles during the preparation process, students have good readiness to take part in the implementation of CBNA, which can be proven by the implementation of CBNA well.